Short-term impact of the smokefree legislation in England on emergency hospital admissions for asthma among adults: a population-based study. Issue 7 (15th April 2013) - Sims, Michelle; Maxwell, Roy; Gilmore, Anna
Abstract : Background: Comprehensive smokefree laws have now been introduced in several jurisdictions. Few studies have examined the association between smokefree laws and asthma in adults and these have limitations, such as lacking appropriate adjustment for long-term trends or having limited statistical power due to small study populations. This study addresses these limitations and evaluates the short-term impact of smokefree legislation in England. It aims to investigate whether the introduction of smokefree legislation on 1 July 2007 was associated with an immediate reduction in emergency hospital admissions for asthma in the adult population, and whether any association differs across regions. Methods: We identified monthly numbers of emergency admissions for asthma (primary diagnosis, 10th revision of the International Classification of Diseases code J45 and J46) in the nine Government Office Regions from April 1997 to December 2010 in the population aged 16 and over. A generalised additive model was fitted that adjusted for seasonality, variation in population size and region-specific, non-linear, long-term trends. Results: Smokefree legislation was associated with an immediate 4.9% (95% CI 0.6% to 9.0%) reduction in emergency admissions for asthma in the adult population. This implies that approximately 1900 emergency admissions for asthma were prevented in each of the first 3 years after legislation was introduced. The reduction in admissions did not vary significantly across regions. Conclusions: Our findings add to the expanding body of evidence that smokefree policies are associated with positive health outcomes. Further research evaluating the impact of legislation in other jurisdictions is needed to support these findings.